Ellipticity dependent excitation and high harmonic generation from intense mid-IR laser pulses in ZnO - Herrmann, Paul; Hollinger, Richard; Korolev, Viacheslav; Zapf, Maximilian; Shumakova, Valentina; Roeder, Robert; Uschmann, Ingo; Pugzlys, Audrius; Baltuska, Andrius; Zurch, Michael; Ronning, Carsten; Spielmann, Christian; et al. (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
In this contribution we experimental examine the ellipticity dependence of strong off resonance absorption and high harmonic generation (HHG) in the wide band gap semiconductor ZnO upon irradiation with intense mid-IR laser pulses. HHG in semiconductors originates from nonlinear intraband currents and interband transitions of the electrons driven by the strong mid-IR fields [Ghimire]. Here, we show that the intra- and interband contribution to HHG in a ZnO thin film are affected differently by the driving laser ellipticity.
CRIS-Team Scopus Importer:2023-04-20